2022
DOI: 10.3389/fpsyg.2022.916234
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a Distance Manager: Managerial Experiences, Perceived Organizational Support, and Job Satisfaction During the COVID-19 Pandemic

Abstract: Due to the COVID-19 pandemic having radically changed the way we now work, many recent studies have focused on employees’ experiences and well-being, their performance and job satisfaction (JSA), and ways to ensure the best support for them when working from home (WFH). However, less attention has been given to managers’ experiences in adapting to the new role of distance management and supporting them with this transition. This study aims to explore how managers experienced distance management, and the percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Rules and regulations regarding ICT use after hours often focus on reducing pressure, but focusing on respecting autonomy appears equally important. As such, dealing with employees who can work anywhere and anytime requires the right support from management ( Ipsen et al, 2022 ). Based on the insights of this paper, a recommendation would be to give employees the choice in how they want to use the ICT tools at their disposal.…”
Section: Discussionmentioning
confidence: 99%
“…Rules and regulations regarding ICT use after hours often focus on reducing pressure, but focusing on respecting autonomy appears equally important. As such, dealing with employees who can work anywhere and anytime requires the right support from management ( Ipsen et al, 2022 ). Based on the insights of this paper, a recommendation would be to give employees the choice in how they want to use the ICT tools at their disposal.…”
Section: Discussionmentioning
confidence: 99%
“…This also applies to line managers. Ipsen et al ( 2022 ) states that managers found their work as remote managers more demanding because they worked more hours. Workplace innovation, as implemented in organizations before the pandemic, can be expected to act as a contextual factor enabling line managers to maintain their wellbeing, as control and responsibility are shared on a wider basis within the organization.…”
Section: Theorymentioning
confidence: 99%
“…The coronavirus pandemic has acted as a catalyst for organisational change, disrupting historic ways of working, and spearheading organisations towards the next evolution of their working environments in the post-industrial era (Gherson & Gratton, 2022). Pre-pandemic working environments saw between 3-5% of US and European employees working from home for some part of the week (Afota et al, 2022;Ipsen et al, 2022). However, in the last three years, we have witnessed the creation of more opportunities than ever before for largescale remote, hybrid, and flexible working practices (Desilver, 2020).…”
Section: Introductionmentioning
confidence: 99%